The joy of [pi] - Blatner, David (London : Penguin Books, 1997)
No number has captured the attention and imagination of people throughout the ages as much as the ratio of a circle's circumference to its diameter. Pi or ? as it is symbolically known, is infinite and, in this book it proves to be infinitely intriguing. The author explores the many facets of pi and humankind's fascination with it, from the ancient Egyptians and Archimedes to Leonardo da Vinci and the modern-day Chudnovsky brothers, who have calculated pi to eight billion digits with a homemade supercomputer. He recounts the history of pi and the quirky stories of those obsessed with it. Sidebars document fascinating pi trivia (including a segment from the O. J. Simpson trial). Dozens of snippets and factoids reveal pi's remarkable impact over the centuries. Mnemonic devices teach how to memorize pi to many hundreds of digits (or more, if you're so inclined). Pi inspired cartoons, poems, limericks, and jokes offer delightfully'square' pi humor. And, to satisfy even the most exacting of number jocks, the first one million digits of pi appear throughout the book.
[ch. 1]. Introduction: Why pi? -- [ch. 2]. History of pi -- [ch. 3]. Chudnovsky brothers -- [ch. 4]. Symbol -- [ch. 5]. Personality of pi -- [ch. 6]. Circle squarers -- [ch. 7]. Memorizing pi.
Includes bibliographical references (page [123]) and index.
Keywords: Pi; Mathematics; Transcendental numbers